Review of deprescribing processes and development of an evidence‐based, patient‐centred deprescribing process. (October 2014) - Reeve, Emily; Shakib, Sepehr; Hendrix, Ivanka; Roberts, Michael S.; Wiese, Michael D.
<x xml:space="preserve">Abstract</x> Inappropriate use of medication is widespread, especially in older people, and is associated with risks, including adverse drug reactions, hospitalization and increased mortality. Optimization of appropriate medication use to minimize these harms is an ongoing challenge in healthcare. The term 'deprescribing' has been used to describe the complex process that is required for safe and effective cessation of medication. Patients play an important role in their own health and, while they may complain about the number of medications they have to take, they may also be reluctant to cease a medication when given the opportunity to do so. A review of previously proposed deprescribing processes and relevant literature was used to develop the patient‐centred deprescribing process, which is a five‐step cycle that encompasses gaining a comprehensive medication history, identifying potentially inappropriate medications, determining whether the potentially inappropriate medication can be ceased, planning the withdrawal regimen (e.g. tapering where necessary) and provision of monitoring, support and documentation. This is the first deprescribing process developed using knowledge of the patients' views of medication cessation; it focuses on engaging patients throughout the process, with the aim of improving long‐term health outcomes. Despite a comprehensive review of the literature, there is still a lack in the evidence base on which to conduct deprescribing. The next step in broadening the evidence to support deprescribing will be to test the developed process to determine feasibility in the clinical setting.